Progression of cardiac allograft vascular disease as assessed by serial intravascular ultrasound: correlation to immunological and non-immunological risk factors. Issue 5 (1st November 2000) - Pethig, K; Klauss, V; Heublein, B; Mudra, H; Westphal, A; Weber, C; Theisen, K; Haverich, A
Abstract : OBJECTIVE: To characterise the severity and progression of cardiac allograft vascular disease (CAVD) in a large patient cohort, and to evaluate possible immunological and non-immunological risk factors for progression. DESIGN: A prospective observational study using intravascular ultrasound. SETTING: Two university hospitals. PATIENTS AND MAIN OUTCOME MEASURES: Changes in focal plaque, lumen, and total vessel area (worst site method) were assessed at baseline and after 12.1 (2.8) months (mean (SD)) of follow up in a cohort of 96 patients (79 male, 17 female; mean age 48.7 (9.6) years; time post-transplant 26.0 (32.4) months). RESULTS: Overall, the mean (SD) intimal index of worst sites increased by 6.7 (8.8)%. The increase in the first 12 months was 7.5 (9.4)%, v 5.9 (8.0)% after the first year (NS). Analysing immunological and non-immunological risk factors (age, underlying disease, sex, donor age, immunosuppression, cytomegalovirus, rejection episodes, cholesterol), low density lipoprotein (LDL) cholesterol was found to be the most important predictor of severe progression (as defined by an increase in intimal index of ⩾ 15% (p = 0.01). CONCLUSIONS: Progression of CAVD is characterised by a continuing increase in intimal hyperplasia, especially within the first year after heart transplantation. LDL cholesterol is an important predictor of major progression.